2004
DOI: 10.1080/02687030444000390
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and short‐term effects of contextual priming on word retrieval in aphasia

Abstract: Background: Many therapy techniques for word retrieval disorders use some form of priming to improve access to words. Priming can facilitate or interfere with naming under different circumstances. We examined effects of priming when combined with semantic or phonological context (training words in groups that are semantically or phonologically related) and how these effects interact with the type of naming impairment (semantically or phonologically based). Aims: We addressed three questions (1) Are word retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…A number of researchers adopt the approach of a by-items statistical analysis (e.g., Abel et al, 2005;Best et al, 1997;Martin, Fink, Laine, & Ayala, 2004), as is conventional and uncontroversial in the field of cognitive neuropsychological case studies not involving therapy. The tests used take advantage of the fact that the same items are usually repeated in each probe.…”
Section: Statistical Analysis By Itemsmentioning
confidence: 99%
“…A number of researchers adopt the approach of a by-items statistical analysis (e.g., Abel et al, 2005;Best et al, 1997;Martin, Fink, Laine, & Ayala, 2004), as is conventional and uncontroversial in the field of cognitive neuropsychological case studies not involving therapy. The tests used take advantage of the fact that the same items are usually repeated in each probe.…”
Section: Statistical Analysis By Itemsmentioning
confidence: 99%
“…In contrast to IL, he benefited from training with a phonological context but not with semantic context. Martin, Fink, Laine, and Ayala (2004) investigated immediate and short-term effects of contextual repetition priming on naming abilities of 11 aphasic individuals. In all but one of the participants, they found that contextual priming had an immediate interference effect on naming (increased errors on naming probes during training in at least one context), but was facilitative for all participants in the short term (significantly better naming on a post-test 5 minutes after treatment).…”
mentioning
confidence: 99%
“…Contextual priming treatment involves intensive repetition of stimulus items presented in sets that are unrelated, semantically related, phonologically related or both semantically and phonologically related (Cornelissen et al, 2003;Martin, Fink, Laine, & Ayala, 2004;Martin & Laine, 2000;Renvall et al, 2003). Of the participants who underwent CP treatment, individuals with predominantly phonological impairments (e.g., LP, YK, Martin & Laine, 2000;JL, Renvall et al, 2003) demonstrated short-term facilitative effects in naming accuracy.…”
Section: Hendricks Nicholas Zipsementioning
confidence: 97%